Innovative nuggets with pangasius fish and moringa leaf flour to enhance adolescent girls' health - Nurul Hindaryani; Fahmi Hafid (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Chronic energy deficiency (CED) in Indonesian adolescent girls is primarily caused by an unbalanced diet that leads to energy and protein deficiencies. Understanding how CED affects the physical development and health of girls is crucial as it may potentially impact their quality of life in the future. This study aimed to evaluate the acceptability and protein content of nuggets formulated with pangasius and moringa leaf flour. The true experimental design was the Testing Service Unit Laboratory, Faculty of Pharmacy, Universitas Airlangga, from April to July 2024. Nuggets with three different formulations were tested organoleptically by 25 panelists, and organoleptic data were analyzed using SPSS and statistically tested using Non-Parametric Testing. The results indicated that NG02 had the highest organoleptic scores for color, aroma, and taste, whereas NG01 had the highest protein content (15.36 %). Statistical analysis revealed no significant differences (p > 0.05) in color, taste, aroma, or texture among the three formulations. In conclusion, despite NG02 being the preferred protein, NG01's higher protein content suggests that it may better address CED in adolescent girls.